The Rage Attack Questionnaire-Revised (RAQ-R): Assessing Rage Attacks in Adults With Tourette Syndrome - Müller-Vahl, Kirsten R.; Kayser, Lena; Pisarenko, Anna; Haas, Martina; Psathakis, Nikolas; Palm, Lisa; Jakubovski, Ewgeni (Frontiers in Psychiatry, 2020)
Although defined by the presence of tics, most patients with Gilles de la Tourette syndrome (TS) also suffer from different psychiatric disorders. While much is known about clinical characteristics of comorbidities such as attention deficit/hyperactivity disorder (ADHD), obsessive compulsive disorder (OCD), depression, and anxiety disorders, only very little is known about rage attacks. Most of this data is based on small studies in children. Until today no larger studies have been performed in adults with TS – not least because of the lack of validated instruments. The aim of this study was to develop a new assessment and investigate rage attacks in a large sample of adults with TS and healthy individuals. Based on a parent questionnaire for children with TS, we generated 27 items for a revised version of a rage attack questionnaire (RAQ-R) and tested factor structure, internal consistency as well as convergent and discriminant validity. We used an online survey and included 127 patients with TS and 645 control subjects. In addition to the RAQ-R, we used several other self-assessments to measure tic severity, quality of life as well as several psychiatric symptoms including ADHD, OCD, depression, anxiety, and impulsivity. Based on expert option and statistical analyses (including item-total correlation, skewness, inter-item correlation, and principal component analysis (PCA)), we performed an item reduction resulting in a final, 22-items version of the RAQ-R (range, 0-66). Investigating internal consistency, discriminant validity, test reliability, and factor structure, the RAQ-R demonstrated good to excellent quality criteria. A preliminary cut-off value of 21.5 was defined for problematic rage attacks. As assessed by RAQ-R, rage attacks were significantly more common in patients with TS comparted to controls (p<0.001). Rage attacks could be clearly differentiated from the phenomenon of impulsivity. Although rage attacks occurred more often in individuals with ADHD, they were also found in patients with “TS only”, independently from comorbid ADHD, impulsivity, and OCD. Rage attacks were found to significantly influence patients’ quality of life. Thus, from our data based on a large sample it is suggested that rage attacks represent a discrete comorbidity in adults with TS.